2004
DOI: 10.1007/s00464-004-9001-z
|View full text |Cite
|
Sign up to set email alerts
|

Should peritoneal tears be routinely closed during laparoscopic total extraperitoneal repair of inguinal hernias? A reappraisal

Abstract: These data demonstrate that PTs do not have to be routinely closed and the majority of cases may be safely managed without peritoneal closure. We have not observed any intra- or postoperative complications that could be attributed to peritoneal tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
(19 reference statements)
2
27
0
4
Order By: Relevance
“…In their comparative study, Khoury et al found that patients who underwent TEP received less narcotic analgesic than those underwent TAPP and were discharged more frequently on the operative day [20]. Although the choice is not based on any solid scientific data, most surgeons prefer open repair or TAPP in complicated cases, including incarcerated hernias, very large scrotal hernias, and for patients who have undergone previous lower abdominal surgery or pelvic surgeries such as radical prostatectomy [21,22]. Moreover, some surgeons claim that previous radical prostatectomy should contraindicate a laparoscopic approach because of the associated scarring in the preperitoneal space [23].…”
Section: Discussionmentioning
confidence: 96%
“…In their comparative study, Khoury et al found that patients who underwent TEP received less narcotic analgesic than those underwent TAPP and were discharged more frequently on the operative day [20]. Although the choice is not based on any solid scientific data, most surgeons prefer open repair or TAPP in complicated cases, including incarcerated hernias, very large scrotal hernias, and for patients who have undergone previous lower abdominal surgery or pelvic surgeries such as radical prostatectomy [21,22]. Moreover, some surgeons claim that previous radical prostatectomy should contraindicate a laparoscopic approach because of the associated scarring in the preperitoneal space [23].…”
Section: Discussionmentioning
confidence: 96%
“…Several researchers have reported that it is feasible for experienced hands to perform TEP hernia repair for patients with a previous lower abdominal operation [10][11][12]. The clinical setting of an inguinal hernia after previous lower abdominal surgery is not very frequent, precluding any attempt to conduct an ideal clinical trial.…”
Section: Discussionmentioning
confidence: 98%
“…Als Ursache zeigt sich dann oftmals ein Hineinrutschen von Darmanteilen in Peritonealdefekte. Vor diesem Hintergrund wird die Notwendigkeit eines konsequenten Verschlusses solcher Peritonealdefekte diskutiert [43].…”
Section: Komplikationsspektrumunclassified